Auditor characteristics on tax avoidance by non-financial companies: Evidence from the Indonesia Stock Exchange - Rafli Prastiatry Zain; Nurmadi Harsa Sumarta; Prihatnolo Gandhi Amidjaya (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
Tax revenue realization in Indonesia is not inseparable from tax avoidance by business entities. The research was conducted to examine the effect of auditor characteristics as proxied by auditor industry specialization, audit tenure, and audit opinion on tax avoidance by non-financial companies listed on the IDX. This study used a set of panel data that consisted of non-financial companies listed on the IDX operating in the 2017-2020 period. The data were obtained from the companies’ annual report. The result of this study demonstrated that auditor industry specialization had a significant positive effect on tax avoidance, while audit tenure did not affect tax avoidance. There was a positive relationship between audit opinion and tax avoidance. This research has limitations as it was only conducted for a short period. Further research can develop this model by including variables which were excluded from this study and involving more samples and sectors of the research objects.